2021
DOI: 10.7717/peerj.10691
|View full text |Cite
|
Sign up to set email alerts
|

The association between serum uric acid and diabetic complications in patients with type 2 diabetes mellitus by gender: a cross-sectional study

Abstract: Background The relationship between serum uric acid (SUA) and several diabetic complications or co-morbidities remains a matter of debate. The study aims to explore the association between SUA levels and the prevalence of non-alcoholic fatty liver disease (NAFLD), diabetic retinopathy (DR), diabetic nephropathy (DN) and diabetic peripheral neuropathy (DPN) in patients with type 2 diabetes mellitus (T2DM). Methods A total of 2,809 participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 49 publications
3
17
0
1
Order By: Relevance
“…The literature search identified 2613 papers, after duplication removal. After abstract evaluations, 16 studies were considered for the full text analysis [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] (Figure 1). Three studies have been excluded, since one is a duplication of previously published results [45], and two works did not report the prevalence of neuropathy in NAFLD positive and negative patients [43,44] (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…The literature search identified 2613 papers, after duplication removal. After abstract evaluations, 16 studies were considered for the full text analysis [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] (Figure 1). Three studies have been excluded, since one is a duplication of previously published results [45], and two works did not report the prevalence of neuropathy in NAFLD positive and negative patients [43,44] (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Serum creatinine (SCr), a biosynthetic product of phosphocreatine metabolism in muscle, is widely used in clinical practice to assess renal function and is more direct and readily available than glomerular filtration rate (GFR). Several clinical studies have shown that even within the normal range, higher SCr is strongly associated with the risk of several diseases, such as cardiovascular disease and diabetes [ 16 , 17 ]. Currently, few clinical studies have investigated the relationship between HS and SCr levels and HS-accompanied fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“… 22 , 33 Other studies have reported that increased SUA is more harmful to women than to men. 34 , 36 38 A study of a Chinese coastal population found that each standard deviation increase in SUA was independently associated with a 1.68-µm increase in retinal venous caliber in women but not significantly in men. 39 This study noted that women's SVD measurements appeared to be more sensitive to elevated SUA levels than men's.…”
Section: Discussionmentioning
confidence: 99%